1980
DOI: 10.21236/ada085396
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Success Chances of Recruits Entering the Navy (SCREEN)

Abstract: ' interest. 5 2. This Research Contribution was prepared in connection Z ' with CNA's study of Personnel Management in the All V Volunteer Force. It reports the updating of a screening technique (SCREEN) for controlling first-year attrition that was developed on regular Navy recruits during the #_ first year of the AVF. SCREEN has been used in qualifying applicants for enlistment since 1976. The LL ' technique is applied to regular Navy recruits in 1977 0 •and extended to reservists in the Active-Mariner progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Married Soldiers had longer enlistment times than single Soldiers (247). Other studies (72,163) found a slightly lower attrition rate among Navy men with dependents regardless of education, age, race or AFQT category. The reasons for these conflicting data are not clear.…”
Section: (5) Marital Status and Dependentsmentioning
confidence: 75%
See 2 more Smart Citations
“…Married Soldiers had longer enlistment times than single Soldiers (247). Other studies (72,163) found a slightly lower attrition rate among Navy men with dependents regardless of education, age, race or AFQT category. The reasons for these conflicting data are not clear.…”
Section: (5) Marital Status and Dependentsmentioning
confidence: 75%
“…The AFQT categories have been used in many studies of attrition. Higher AFQT scores are associated with lower attrition (19,25,36,42,43,60,63,64,70,92,111,114,121,145,150,163,167,172,199,208,220,236,247,251,253,268), but the effect is not a strong one. Several studies found that the effect of AFQT on first-term attrition among Sailors and Marines was not diminished when high school diploma status was considered (43,61,70,98).…”
Section: B Cognitive/psychosociai Factors (1) Armed Forces Qualificamentioning
confidence: 95%
See 1 more Smart Citation
“…Survivability is measured by successful completion of a recruit's obligated service. The dominant predictor of survival, as confirmed by numerous studies, is education [1].…”
Section: Introductionmentioning
confidence: 87%
“…The Attrition Component evaluates the utility of assigning a given individual to a given rating, based upon the probability of surviving the first term of enlistment and the attrition severity index (ASI) of the rating. The person characteristic measure is the SCREEN table (Lockman, 1977) and the rating characteristic measure is the ASI. The SCREEN score, which is based upon the individual's education credential status, AFQT score, and age, reflects the probability of successfully completing the first term of his enlistment.…”
Section: Attrition Componentmentioning
confidence: 99%